Trabalho terceirizado: uma representação da formalidade precária? Da caracterização geral à especificidade do setor de limpeza em Santa Maria/RS no contexto dos anos 2000 - Andreta, Rachel Loureiro (2016)
This study aimed to analyze the relation between the third party work regarding the cleaning industry and casualization. This study was carried out in the context of the 2000‟s during the PT federal governments. It was taken into consideration the increasing in the formal work that consequently increased the third party works during this period and; in sequence, it was made an attempt to understand if this type of work allowed an economic and social growth for the workers or if it improved their condition of vulnerability. To do so, this research was carried out in two moments: first, it was done a statistical and descriptive survey about the third party work in Brazil, especially regarding the city of Santa Maria/RS, in order to verify the location and extension of this phenomenon in the period of 2004 to 2014. Secondly, observations and interviews were carried out with workers from the third party cleaning industry in Santa Maria/RS, to analyze their work and life conditions. The collected data allowed us to identify that the third party work, regarding the cleaning industry, has casualization characteristics such as low payments, instability, no health insurance and workplace safety; third party workers are treated differently from the permanent ones; and there are impairment of the relations and the social invisibility happens as well. The third party work presents itself as a two-way street . Despite the negative effects and all vulnerability that it represents, it was observed that having a formal work register meant an advance to such workers because, the great majority, used to work informally or receiving a salary without any registration. Thus, it is understood that the third party work, in the 2000‟s during the PT federal governments, represents the precarious formality (SOUZA, 2012). In other words, in spite of being considered a formal work, the workers are submitted to precarious work conditions (which go beyond the labor market) and such conditions are disguised behind the so-called formal work register.